GIS Application for Estimation of Concentration Times in the Middle Basin of Sinu River, Colombia - Tapias Contreras, Hernán José; Caraballo Hernández, Viviana Paola (Rev. Téc. Fac. Ing. Univ. Zulia, 2023)
The time of concentration (Tc) is one of the most important factors when sizing hydraulic works, since it is one of the main inputs in a hydrological analysis. In this sense, the objective of this research was to determine the physicomorphometric parameters using geographic information systems (GIS) and manual estimations of Tc in the middle basin of the Sinú River, Colombia, and then perform a linear correlation analysis (r) and model variability (r2). To this end, we sought to quantitatively demonstrate how Tc results vary when calculated by means of 16 empirical equations and how morphometric variables calculated with the ArcGIS 10.8 program influence these calculations. A lack of correspondence between the different methods used was observed, which allows us to glimpse the problem of having the data of a hydrological analysis poorly represented and applied in a project, in addition to the need to design a model that allows optimizing the use of these equations with GIS.